Sanfilippo Type B disease: A diagnostic approach through enzymatic and molecular analysis in Colombia (2021)
Glycosaminoglycan metabolism disorders bring together a group of alterations of genetic origin whose effect is the progressive intralysosomal accumulation of GAGs. Affected individuals are compromised in a multisystemic way causing, among other clinical manifestations, coarse facial features, short stature, multiple skeletal dysplasia, joint stiffness, visceromegaly and developmental delay. The diagnostic approach to these disorders represents a challenge in our context since the required biochemical tests are specialized and only performed in major cities. This makes it difficult to have access to affected patients whose geographical location is distant and therefore, the use of samples collected in solid-phase represents an advantage for the study of high-risk populations. The present study aims to report the experience of twenty years of selective screening by assessing enzyme activity in dried blood spots (DBS) collected on filter paper and leukocyte extracts. The deficiency of the enzymes here studied has been associated with Mucopolysaccharidosis I, II, IIIB, IVA, IVB, VI and VII. The present study assessed a population of 8,239 patients referred for clinical suspicion of MPS. Fluorometric endpoint methods using 4-methylumbelliferone-labeled substrates were used. This study allowed us to establish reference values in the Colombian population for ?-L-iduronidase, iduronate 2-sulfatase, ?-N-acetylglucosaminidase, N-acetylglucosamine-6-sulfate sulfatase, ?-galactosidase, arylsulfatase B and ?-glucuronidase, in DBS and leukocytes. In addition, incidence values were calculated for each of MPS. This study offers very useful information for the health system, the scientific community and facilitates the diagnostic definition of these metabolic disorders in the country.